A halide-based perovskite film, and a preparation method and application thereof

CN123022100APending Publication Date: 2026-10-30HUANENG CLEAN ENERGY RES INST +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611337684.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

部分添加剂与钙钛矿组分之间的相互作用较弱或不可控,容易在薄膜退火过程中挥发或聚集,导致效果不稳定;而另一些添加剂虽然能形成较强的化学键合,却可能引入过多的空间位阻,反而干扰钙钛矿的有序成核和晶体生长,使得薄膜的致密性和均匀性下降

Benefits of technology

通过将配合物分子与卤化铅混合后进行球磨,利用机械力化学作用使配合物分子与卤化铅充分发生配位反应,形成结构均一卤化铅配合物。再将该配合物引入前驱体,确保了添加剂在后续过程中的均一性和可控性,避免了直接将氨基酸等分子添加钙钛矿前驱体溶液带来的溶解不完全、局部团聚等带来的前驱体胶体稳定性下降甚至产生沉淀的不稳定问题;碘化铅配合物加入前驱体后,其中的配体分子因已与Pb²+形成配位键,不会在溶液中自由游走或与主前驱体中的Pb²+发生不可控的预反应。在涂覆成膜及后续退火处理过程中,该配合物一方面通过空间位阻效应调控钙钛矿晶体的生长速率和取向,抑制过快成核带来的无序生长,从而减少晶界缺陷和针孔,获得致密均匀、结晶度高的钙钛矿薄膜,另一方面在退火过程中自发向晶界及薄膜表面定向迁移富集,残留于晶界处的配合物有效缝合相邻晶粒之间的缝隙并钝化未配位的铅离子缺陷,富集于薄膜表面的配合物自组装形成疏水屏障层,有效阻隔水氧分子的侵蚀。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application belongs to the technical field of perovskite batteries, and relates to a perovskite thin film based on a lead halide complex and a preparation method and application thereof. The application comprises the following steps: mixing a complex molecule with lead halide and performing ball milling to obtain a lead halide complex; adding the lead halide complex into a perovskite precursor solution to obtain a perovskite precursor solution containing a lead halide complex additive; providing a substrate, coating the perovskite precursor solution containing the lead halide complex additive on the substrate, and performing annealing treatment to obtain a perovskite thin film. The application realizes the synergistic improvement of crystalline quality improvement, defect passivation and long-term stability, thereby significantly improving the photoelectric conversion efficiency and operation life of a perovskite solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of perovskite battery technology, and relates to a perovskite thin film based on lead halide complex, its preparation method and application. Background Technology

[0002] Organic-inorganic hybrid perovskite materials, with their ABX3 crystal structure (where the A-site is typically an organic cation such as methylamine or formamidinium, or a cesium ion; the B-site is a metal ion such as lead or tin; and the X-site is a halide ion), exhibit excellent light absorption coefficients, tunable band gaps, long carrier diffusion lengths, and low-cost solution processing performance. However, perovskites are highly susceptible to decomposition or phase transitions under environmental stresses such as light, high temperature, humidity, and oxygen. For example, methylamine perovskite readily degrades into lead iodide and organic salts under humid conditions, while formamidinium perovskite may undergo a non-photoactive yellow phase transition at room temperature. These degradation processes directly lead to rapid decline in device efficiency or even complete failure. To address these stability challenges, researchers have explored various strategies, including composition engineering (such as mixed ion substitution at the A-site and X-site), interface engineering (such as inserting a passivation layer between the perovskite layer and the charge transport layer), encapsulation technology, and additive engineering.

[0003] Additive engineering has attracted much attention due to its ease of operation and significant effects. By introducing small organic molecules, polymers, or inorganic salts with specific functional groups into the perovskite precursor solution, crystallization kinetics can be controlled, film defects reduced, and grain boundaries and surface dangling bonds passivated, thereby improving film quality and device stability to a certain extent. For example, adding organic molecules containing carbonyl, amino, or thiocyanate groups to the precursor solution utilizes these functional groups to form coordination interactions with uncoordinated lead ions in the perovskite, inhibiting non-radiative recombination and delaying the degradation process. Some additives have weak or uncontrollable interactions with perovskite components, easily volatilizing or aggregating during film annealing, leading to unstable effects; while other additives, although forming strong chemical bonds, may introduce excessive steric hindrance, interfering with the ordered nucleation and crystal growth of the perovskite, resulting in decreased film density and uniformity. Summary of the Invention

[0004] To address the problems in the prior art, this invention provides a perovskite thin film based on lead halide complexes, its preparation method, and its application. This achieves a synergistic improvement in crystal quality, defect passivation, and long-term stability, thereby significantly enhancing the photoelectric conversion efficiency and lifespan of perovskite solar cells.

[0005] To achieve the above objectives, the present invention employs the following technical solution: In a first aspect, the present invention provides a method for preparing perovskite thin films based on lead halide complexes, comprising the following steps: The complex molecules were mixed with lead halide and then ball-milled to obtain lead halide complexes; The lead halide complex was added to the perovskite precursor solution to obtain a perovskite precursor solution containing the lead halide complex additive. A substrate is provided, and the perovskite precursor solution containing lead halide complex additives is coated onto the substrate, followed by annealing to obtain a perovskite film.

[0006] Preferably, the complex molecule is an amino acid or disodium ethylenediaminetetraacetate.

[0007] Preferably, the lead halide is lead iodide, lead bromide, or lead chloride.

[0008] Preferably, the molar ratio of the complex molecule to lead halide is (1~3):1.

[0009] Preferably, the method for preparing the perovskite precursor solution includes: The perovskite precursor solution is obtained by mixing halide salt AX, metal halide BX2, and solvent; wherein A is methylamine ion, formamidinium ion, or cesium ion; B is lead ion; X is halide ion; and the solvent includes one or more of N,N-dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone.

[0010] Preferably, the molar ratio of the halide salt AX to the halide metal BX2 is 1:(0.8~1.5).

[0011] Preferably, the molar ratio of the lead halide complex to the metal halide BX2 is (0.01~0.05):1.

[0012] Preferably, the ball milling time is 10-60 minutes, and the ball milling speed is 200-600 rpm; the annealing temperature is 100-150℃, and the annealing time is 10-30 minutes.

[0013] Secondly, the present invention provides a perovskite thin film based on lead halide complexes.

[0014] Thirdly, the present invention provides an application of a perovskite thin film based on lead halide complexes in the field of perovskite battery technology, wherein the perovskite thin film serves as the perovskite layer of a perovskite battery.

[0015] Compared with the prior art, the present invention has the following beneficial effects: By ball milling a mixture of the complex molecules and lead halide, mechanochemical reactions are utilized to ensure sufficient coordination between the complex molecules and lead halide, forming a structurally homogeneous lead halide complex. This complex is then introduced into the precursor, ensuring the homogeneity and controllability of the additive in subsequent processes. This avoids the instability problems caused by directly adding amino acids and other molecules to the perovskite precursor solution, such as incomplete dissolution, local agglomeration, decreased colloidal stability of the precursor, or even precipitation. After the lead iodide complex is added to the precursor, its ligand molecules, having already bound Pb²⁻, further enhance its properties. + It forms coordination bonds and will not migrate freely in solution or bind with Pb² in the main precursor. + An uncontrollable pre-reaction occurs. During the coating and subsequent annealing processes, the complex, on the one hand, regulates the growth rate and orientation of perovskite crystals through steric hindrance, suppressing disordered growth caused by excessively rapid nucleation, thereby reducing grain boundary defects and pinholes, and obtaining a dense, uniform, and highly crystalline perovskite film. On the other hand, during annealing, it spontaneously migrates and accumulates towards the grain boundaries and film surface. The complex remaining at the grain boundaries effectively sutures the gaps between adjacent grains and passivates uncoordinated lead ion defects. The complex enriched on the film surface self-assembles to form a hydrophobic barrier layer, effectively blocking the erosion of water and oxygen molecules. Detailed Implementation

[0016] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used in the specification and claims are explained and defined in general below. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.

[0017] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.

[0018] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values ​​(including integers and fractions) within those ranges.

[0019] In this article, unless otherwise specified, “contains,” “includes,” “containing,” “has,” or similar terms cover the meanings of “composed of” and “mainly composed of,” for example, “A contains a” covers the meanings of “A contains a and others” and “A contains only a.”

[0020] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.

[0021] The first objective of this invention is to provide a method for preparing perovskite thin films based on lead halide complexes, comprising the following steps: The complex molecules (such as amino acids or disodium ethylenediaminetetraacetate) are mixed with lead halides (such as lead iodide, lead bromide or lead chloride) at a molar ratio of (1~3):1 and then placed in a ball mill. The mixture is ball-milled at a speed of 200~600 rpm for 10~60 minutes to allow the complex molecules and lead halides to undergo a full coordination reaction through mechanochemical action, resulting in lead halide complex powder with uniform particle size and high reactivity. The lead halide complex was introduced as an additive into the perovskite precursor solution. After addition, the mixture was stirred to ensure uniform dispersion of the complex in the perovskite precursor solution. The perovskite precursor solution containing the complex additive was then uniformly coated onto the substrate by spin coating, slot coating, or blade coating. An anti-solvent could be used during the coating process to promote the orderly precipitation of the perovskite mesophase. The film was then annealed at 100-150°C for 10-30 minutes to obtain the perovskite film.

[0022] In this method, the lead halide complex prepared by ball milling is added to the precursor solution as an additive. The amino and carboxyl groups in the complex molecule can form a strong coordination interaction with the lead ions in the perovskite component. During the nucleation and crystallization process, a steric hindrance effect is generated, which effectively regulates the growth rate and orientation of the perovskite crystal, inhibits the disordered growth caused by excessively rapid nucleation, thereby reducing grain boundary defects and pinholes, and obtaining a dense, uniform, and highly crystalline perovskite film. At the same time, the lead halide complex remaining on the film surface and at the grain boundaries can form a physicochemical barrier. On the one hand, it effectively blocks the invasion of water and oxygen molecules through hydrophobic groups. On the other hand, it continuously passivates dangling bonds and defect states at the surface and grain boundaries through uncoordinated active sites, inhibiting ion migration and non-radiative recombination, thereby synergistically improving the long-term stability of the perovskite film under environmental stresses such as damp heat and light.

[0023] For example, the method for preparing the perovskite precursor solution includes: The perovskite precursor solution is obtained by mixing halide salt AX, metal halide BX2, and solvent; wherein A is methylamine ion, formamidinium ion, or cesium ion; B is lead ion; X is halide ion; the solvent includes one or more of N,N-dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone; wherein the molar ratio of halide salt AX to metal halide BX2 is 1:(0.8~1.5), so that the components in the precursor solution can maintain a uniform and stable dispersion state within a wide ratio range.

[0024] In addition, an appropriate amount of crystallization regulating additives can be added to the perovskite precursor solution. The crystallization regulating additives are methylamine chloride or formamidinium chloride. These ammonium salt additives can regulate the colloidal chemical environment in the solution through chemical coordination and hydrogen bonding with the precursor components during the perovskite film formation process.

[0025] For example, the molar ratio of the lead halide complex to the metal halide BX2 is (0.01~0.05):1. Within this ratio range, the lead halide complex can effectively regulate the crystallization kinetics through the steric hindrance effect during the nucleation stage to obtain a high-quality perovskite film with uniform grain size and low defect density. It can also fully migrate to the grain boundaries and film surface during the annealing process to form a chemical barrier of moderate thickness and complete coverage, effectively blocking water and oxygen erosion and inhibiting ion migration. Thus, without sacrificing device efficiency, it maximizes the long-term operational stability of perovskite solar cells and fully realizes the synergistic gain effect of improving crystal quality and strengthening surface passivation.

[0026] The second objective of this invention is to provide a perovskite thin film based on lead halide complexes. Unlike traditional perovskite thin films that are simply doped or surface-coated with additives, the lead halide complexes in this invention are not uniformly distributed throughout the bulk phase. Instead, based on the difference in chemical affinity between specific functional groups (such as amino, carboxyl, and hydroxyl groups) in the complex molecules and the perovskite components, they spontaneously migrate and accumulate towards grain boundaries and the film surface during annealing and crystallization. On the one hand, the complexes enriched at the grain boundaries can effectively suture the gaps between adjacent grains, blocking the rapid diffusion channels of external water and oxygen along the grain boundaries, and at the same time, passivating the grain boundaries through coordination. The presence of uncoordinated lead ion defects inhibits ion migration and aggregation along grain boundaries, significantly enhancing the structural and chemical stability of the film under humid, hot, and electric bias conditions. On the other hand, the complexes enriched on the film surface self-assemble to form a nanoscale hydrophobic barrier layer. Without affecting the effective absorption of light and bulk carrier transport of the underlying perovskite, this layer effectively prevents the penetration of water molecules and the diffusion of oxygen, greatly delaying the decomposition and phase transition process of the perovskite. At the same time, the polar functional groups contained in this surface barrier layer can also form good interfacial contact with the subsequently deposited electron transport layer or hole transport layer, improving energy level matching and charge extraction efficiency.

[0027] A third objective of this invention is to provide an application of a perovskite thin film based on lead halide complexes in the field of perovskite battery technology, wherein the perovskite thin film serves as the perovskite layer of a perovskite battery.

[0028] Specifically, the perovskite solar cell comprises, from bottom to top, a transparent conductive substrate, a hole transport layer, a perovskite light-absorbing layer, an electron transport layer, a buffer layer, and a metal top electrode. The transparent conductive substrate is made of FTO (fluorine-doped tin oxide) conductive glass. A NiOx thin film is prepared on the substrate using magnetron sputtering as the hole transport layer, and then annealed at 300-400°C for 30-60 minutes to obtain good crystallinity and hole extraction capability. Above the hole transport layer is the perovskite light-absorbing layer prepared in this invention. This layer is prepared by spin-coating a perovskite precursor solution containing lead halide complex additives, followed by annealing at 100-120°C for 20-30 minutes. This layer performs the core functions of light absorption and exciton generation and separation. C is prepared on the perovskite light-absorbing layer using vacuum evaporation. 60 The thin film serves as an electron transport layer for extracting and transporting electrons. A BCP (bath copper spirit) thin film is deposited on top of the electron transport layer as a buffer layer to block holes and reduce interfacial recombination. A metal electrode (such as Au, Ag or Al) with a thickness of 100 nm is prepared on the top layer by vacuum evaporation to serve as the top electrode for collecting charge carriers and conducting external circuits. Furthermore, during the coating process of the perovskite precursor solution, antisolvent treatment is preferably adopted to further optimize the crystal quality and surface morphology of the film. Specifically, the antisolvent treatment refers to adding an appropriate amount of antisolvent to the surface of the wet film when the wet film of the perovskite precursor is not completely dry during the solution film formation process such as spin coating or blade coating. The antisolvent is usually an organic solvent that is miscible with the perovskite precursor solvent (such as DMF, DMSO) but does not dissolve the perovskite components, such as chlorobenzene, toluene, diethyl ether, ethyl acetate or anisole.

[0029] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0030] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. All raw materials used in the following examples are conventional commercially available products with specifications conventional in the art. In this specification and the following examples, unless otherwise specified, "%" refers to weight percentage, "parts" refers to parts by weight, and "ratio" refers to weight proportion.

[0031] Example 1 Step 1: Clean the FTO glass substrate in sequence with acetone, isopropanol, and deionized water, and then dry it for later use.

[0032] Step 2: A NiOx hole transport layer with a thickness of 30 nm is prepared on an FTO glass substrate by magnetron sputtering and then annealed at a temperature of 300 °C for 30 min.

[0033] Step 3: Add 6.6852g of disodium ethylenediaminetetraacetate and 4.61g of lead iodide to a ball mill and ball mill at 300 rpm for 60 minutes to obtain the disodium ethylenediaminetetraacetate-lead iodide complex.

[0034] Step 4: Prepare FA solution with a concentration of 1.5 mol / L according to the stoichiometric ratio. 0.95 Cs 0.05 PbI3 perovskite precursor solution. Specifically, 243.7 mg FAI, 19.49 mg CsI, 691.51 mg PbI2 and 20.3 mg MACl were weighed and placed in a mixing container. 1 mL of a mixed solvent of DMF and DMSO (wherein the volume ratio of DMF to DMSO is 4:1) was added to the mixing container containing the above raw materials to obtain a perovskite solution.

[0035] Step 5: Add 0.03 mmol of disodium ethylenediaminetetraacetate-lead iodide complex to the perovskite solution.

[0036] Step 6: Take 100 μL of perovskite solution and coat it onto the hole transport layer. First, spin coat at 2000 rpm for 10 seconds, then spin coat at 5000 rpm for 40 seconds to form a liquid film. Take 200 μL of chlorobenzene as an anti-solvent and spin coat it onto the liquid film for 15 seconds. Then, anneal the perovskite film on a hot plate at 100°C for 30 minutes to form a perovskite light-absorbing layer with a thickness of 400 nm.

[0037] Step 7: Electron transport layer C is sequentially prepared on the perovskite light-absorbing layer using vacuum evaporation. 60 The layer and the buffer layer BCP layer have thicknesses of 40nm and 5nm, respectively.

[0038] Step 8: Prepare a metal electrode with a thickness of 100 nm on the BCP layer using vacuum evaporation to obtain a perovskite solar cell.

[0039] Example 2 Step 1: Clean the FTO glass substrate in sequence with acetone, isopropanol, and deionized water, and then dry it for later use.

[0040] Step 2: A NiOx hole transport layer with a thickness of 30 nm is prepared on an FTO glass substrate by magnetron sputtering and then annealed at a temperature of 300 °C for 30 min.

[0041] Step 3: Add 2.9238g of lysine and 4.61g of lead iodide to a ball mill and ball mill at 300 rpm for 60 minutes to obtain the lysine-lead iodide complex.

[0042] Step 4: Prepare FA solution with a concentration of 1.5 mol / L according to the stoichiometric ratio. 0.95 Cs 0.05 PbI3 perovskite precursor solution. Specifically, 243.7 mg FAI, 19.49 mg CsI, 691.51 mg PbI2 and 20.3 mg MACl were weighed and placed in a mixing container. 1 mL of a mixed solvent of DMF and DMSO (wherein the volume ratio of DMF to DMSO was 4:1) was added to the mixing container containing the above raw materials to obtain a perovskite solution.

[0043] Step 5: Add 0.03 mmol of the above lysine-lead iodide complex to the perovskite solution.

[0044] Step 6: Take 100 μL of perovskite solution and coat it onto the hole transport layer. First, spin coat it at 2000 rpm for 10 s, and then spin coat it at 5000 rpm for 40 s to form a liquid film. Take 200 μL of chlorobenzene as an anti-solvent and spin coat it onto the liquid film for 15 s. Then, anneal the perovskite film on a hot stage at 100°C for 30 minutes to form a perovskite light-absorbing layer with a thickness of 400 nm.

[0045] Step 7: Electron transport layer C is sequentially prepared on the perovskite light-absorbing layer using vacuum evaporation. 60 The layer and the buffer layer BCP layer have thicknesses of 40nm and 5nm, respectively.

[0046] Step 8: Prepare a metal electrode with a thickness of 100 nm on the BCP layer using vacuum evaporation to obtain a perovskite solar cell.

[0047] Example 3 Step 1: Clean the FTO glass substrate in sequence with acetone, isopropanol, and deionized water, and then dry it for later use.

[0048] Step 2: A NiOx hole transport layer with a thickness of 30 nm is prepared on an FTO glass substrate by magnetron sputtering and then annealed at a temperature of 300 °C for 30 min.

[0049] Step 3: Add 3.103g of histidine and 4.61g of lead iodide to a ball mill and ball mill at 300 rpm for 60 minutes to obtain the histidine-lead iodide complex.

[0050] Step 4: Prepare FA solution with a concentration of 1.5 mol / L according to the stoichiometric ratio. 0.95 Cs 0.05 PbI3 perovskite precursor solution. Specifically, 243.7 mg FAI, 19.49 mg CsI, 691.51 mg PbI2 and 20.3 mg MACl were weighed and placed in a mixing container. 1 mL of a mixed solvent of DMF and DMSO (wherein the volume ratio of DMF to DMSO was 4:1) was added to the mixing container containing the above raw materials to obtain a perovskite solution.

[0051] Step 5: Add 0.03 mmol of the above histidine-lead iodide complex to the perovskite solution.

[0052] Step 6: Take 100 μL of perovskite solution and coat it onto the hole transport layer. First, spin coat it at 2000 rpm for 10 s, and then spin coat it at 5000 rpm for 40 s to form a liquid film. Take 200 μL of chlorobenzene as an anti-solvent and spin coat it onto the liquid film for 15 s. Then, anneal the perovskite film on a hot stage at 100°C for 30 minutes to form a perovskite light-absorbing layer with a thickness of 400 nm.

[0053] Step 7: Using vacuum evaporation, an electron transport layer C60 and a buffer layer BCP are sequentially prepared on the perovskite light-absorbing layer, with thicknesses of 40 nm and 5 nm, respectively.

[0054] Step 8: Prepare a metal electrode with a thickness of 100 nm on the BCP layer using vacuum evaporation to obtain a perovskite solar cell.

[0055] Example 4 Step 1: Clean the FTO glass substrate in sequence with acetone, isopropanol, and deionized water, and then dry it for later use.

[0056] Step 2: A NiOx hole transport layer with a thickness of 30 nm is prepared on an FTO glass substrate by magnetron sputtering and then annealed at a temperature of 300 °C for 30 min.

[0057] Step 3: Add 6.6852g of disodium ethylenediaminetetraacetate and 4.61g of lead iodide to a ball mill and ball mill at 300 rpm for 60 minutes to obtain the disodium ethylenediaminetetraacetate-lead iodide complex.

[0058] Step 4: Prepare FA solution with a concentration of 1.5 mol / L according to the stoichiometric ratio. 0.9 MA 0.05 Cs 0.05 PbI 2.7 Br 0.3 Perovskite precursor solution. Specifically, 230.9 mg FAI, 11.92 mg MAI, 19.49 mg CsI, 82.58 mg PbBr2, 587.78 mg PbI2 and 20.3 mg MACl were weighed and placed in a mixing container. 1 mL of a mixed solvent of DMF and DMSO (wherein the volume ratio of DMF to DMSO is 4:1) was added to the mixing container containing the above raw materials to obtain a perovskite solution.

[0059] Step 5: Add 0.03 mmol of disodium ethylenediaminetetraacetate-lead iodide complex to the perovskite solution.

[0060] Step 6: Take 100 μL of perovskite solution and coat it onto the hole transport layer. First, spin coat at 2000 rpm for 10 seconds, then spin coat at 5000 rpm for 40 seconds to form a liquid film. Take 200 μL of chlorobenzene as an anti-solvent and spin coat it onto the liquid film for 15 seconds. Then, anneal the perovskite film on a hot plate at 100°C for 30 minutes to form a perovskite light-absorbing layer with a thickness of 400 nm.

[0061] Step 7: Electron transport layer C is sequentially prepared on the perovskite light-absorbing layer using vacuum evaporation. 60 The layer and the buffer layer BCP layer have thicknesses of 40nm and 5nm, respectively.

[0062] Step 8: Prepare a metal electrode with a thickness of 100 nm on the BCP layer using vacuum evaporation to obtain a perovskite solar cell.

[0063] Example 5 Step 1: Clean the FTO glass substrate in sequence with acetone, isopropanol, and deionized water, and then dry it for later use.

[0064] Step 2: A NiOx hole transport layer with a thickness of 30 nm is prepared on an FTO glass substrate by magnetron sputtering and then annealed at a temperature of 300 °C for 30 min.

[0065] Step 3: Add 6.6852g of disodium ethylenediaminetetraacetate and 4.61g of lead iodide to a ball mill and ball mill at 300 rpm for 60 minutes to obtain the disodium ethylenediaminetetraacetate-lead iodide complex.

[0066] Step four: Prepare a 0.8 mol / L CsPbI3 perovskite precursor solution according to the stoichiometric ratio. Specifically, weigh 127.17 mg MAI, 207.84 mg CsI, and 368.81 mg PbI2 and place them in a mixing container. Add 1 mL of a mixed solvent of DMF and NMP (wherein the volume ratio of DMF to DMSO is 9:1) to the mixing container containing the above raw materials to obtain the perovskite solution.

[0067] Step 5: Add 0.008 mmol of disodium ethylenediaminetetraacetate-lead iodide complex to the perovskite solution.

[0068] Step 6: Take 100 μL of perovskite solution and coat it onto the hole transport layer. Spin coat at 3000 rpm for 30 seconds to form a liquid film. Then anneal the perovskite film at 150°C for 30 minutes on a hot plate to form a perovskite light-absorbing layer with a thickness of 400 nm.

[0069] Step 7: Electron transport layer C is sequentially prepared on the perovskite light-absorbing layer using vacuum evaporation. 60 The layer and the buffer layer BCP layer have thicknesses of 40nm and 5nm, respectively.

[0070] Step 8: Prepare a metal electrode with a thickness of 100 nm on the BCP layer using vacuum evaporation to obtain a perovskite solar cell.

[0071] Comparative Example 1 The difference from Example 1 is that steps three and five were not performed.

[0072] Test method: The perovskite solar cell devices prepared in Examples 1-3 and Comparative Example 1 were all tested under standard conditions (AM 1.5G spectrum, 1000 W / m²). 2 JV characteristic curves were tested using a solar simulator and a Keithley 2400 source meter under irradiance (25°C).

[0073] The test results are shown in Table 1: Table 1. JV Performance Comparison of Perovskite Solar Cell Devices

[0074] As shown in Table 1, Comparative Example 1, without the addition of lead halide complex additives, had a photoelectric conversion efficiency of only 25.86%. In contrast, Examples 1-3, which added disodium ethylenediaminetetraacetate-lead iodide complex, lysine-lead iodide complex, and histidine-lead iodide complex respectively, all achieved photoelectric conversion efficiencies above 26.5%, with improvements in open-circuit voltage and fill factor. This comparison directly demonstrates that adding lead iodide complexes to perovskite precursors can significantly enhance the overall photoelectric performance of perovskite solar cells.

[0075] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing perovskite thin films based on lead halide complexes, characterized in that, Includes the following steps: The complex molecules were mixed with lead halide and then ball-milled to obtain lead halide complexes; The lead halide complex was added to the perovskite precursor solution to obtain a perovskite precursor solution containing the lead halide complex additive. A substrate is provided, and the perovskite precursor solution containing lead halide complex additives is coated onto the substrate, followed by annealing to obtain a perovskite film.

2. The method for preparing a perovskite thin film based on a lead halide complex according to claim 1, characterized in that, The complex molecule is an amino acid or disodium ethylenediaminetetraacetate.

3. The method for preparing a perovskite thin film based on a lead halide complex according to claim 1, characterized in that, The lead halide is lead iodide, lead bromide, or lead chloride.

4. The method for preparing a perovskite thin film based on a lead halide complex according to claim 1, characterized in that, The molar ratio of the complex molecules to lead halide is (1~3):

1.

5. The method for preparing a perovskite thin film based on a lead halide complex according to claim 1, characterized in that, The method for preparing the perovskite precursor solution includes: The perovskite precursor solution is obtained by mixing halide salt AX, metal halide BX2, and solvent; wherein A is methylamine ion, formamidinium ion, or cesium ion; B is lead ion; X is halide ion; and the solvent includes one or more of N,N-dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone.

6. The method for preparing a perovskite thin film based on a lead halide complex according to claim 5, characterized in that, The molar ratio of the halide salt AX to the halide metal BX2 is 1:(0.8~1.5).

7. The method for preparing a perovskite thin film based on a lead halide complex according to claim 5, characterized in that, The molar ratio of the lead halide complex to the metal halide BX2 is (0.01~0.05):

1.

8. The method for preparing a perovskite thin film based on a lead halide complex according to claim 1, characterized in that, The ball milling time is 10-60 minutes, and the ball milling speed is 200-600 rpm; the annealing temperature is 100-150℃, and the annealing time is 10-30 minutes.

9. A perovskite thin film based on a lead halide complex, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 8.

10. The application of the perovskite thin film based on lead halide complex according to claim 9 in the field of perovskite battery technology, characterized in that, The perovskite film serves as the perovskite layer of the perovskite solar cell.